Heck, Sonogashira, and Hiyama Reactions Catalyzed by Palladium Nanoparticles Stabilized by Tris‐Imidazolium Salt. Issue 14 (4th April 2014) - Planellas, Marc; Moglie, Yanina; Alonso, Francisco; Yus, Miguel; Pleixats, Roser; Shafir, Alexandr
Abstract: Palladium nanoparticles, prepared by the hydrogenation of Pd(dba)2 in the presence of a tris‐imidazolium iodide as stabilizer, act as an efficient catalyst for Heck and copper‐free Sonogashira reactions with a range of aryl iodides and bromides at 0.2 mol‐% Pd loading. Moreover, we describe a convenient protocol for the fluoride‐free Hiyama coupling of vinylsilanes with aryl iodides that involves the use of sodium hydroxide as promoter in a methanol/water mixture. Under the developed conditions, one‐pot, double Heck and Hiyama–Heck reactions are successfully achieved. Abstract : Palladium nanoparticles stabilized by a tris‐imidazolium iodide act as an efficient catalyst for Heck, copper‐free Sonogashira, and fluoride‐free Hiyama coupling reactions. Under the developed conditions, one‐pot, double Heck and Hiyama–Heck reactions have also been successfully achieved.